Conversion of chlorine/nitrogen species and formation of nitrogenous disinfection by-products in the pre-chlorination/post-UV treatment of sulfamethoxazole. (1st September 2019) - Zhang, Tian-Yang; Xu, Bin; Yao, Shijie; Hu, Yaru; Lin, Kuangfei; Ye, Hui; Cui, Changzheng
Abstract: Pre-chlorination and UV disinfection are two common processes in drinking water treatment plants. Sulfamethoxazole (SMX), an antibiotic widely detected in source water, was selected as a precursor to study the conversion of chlorine/nitrogen species and DBP formation in pre-chlorination/post-UV process. The combined chlorine (mainly organic chloramines) produced in pre-chlorination of SMX can self-degrade and release free chlorine back again as pre-chlorination time goes on. With free chlorine dose increasing, the self-degradation rate of combined chlorine increased obviously. But the combined chlorine stopped self-degrading and remained stable around 1 mg-Cl2 /L after adding 0.30 mM chlorine for 30 min. Post-UV treatment after pre-chlorination can enhance the degradation and achieve a complete removal of combined chlorine (including organic chloramines). Deamination occurred during pre-chlorination/post-UV process and deamination amount (-NH2 ) per SMX concentration was 0.19 M/M. Radicals in this process had no obvious influence on chlorine/nitrogen species conversion. Direct chlorination of SMX had the lowest DBP formation potentials while the application of pre-chlorination and UV enhanced them. Compared with UV treatment only, dichloroacetonitrile formation potential of SMX reduced by 1.58 × 10 −3  mol/mol-SMX (17.37 μg/l) after pre-chlorination/post-UV treatment. During pre-chlorination/post-UV/final-chlorination treatment of SMX, Br − and natural organic matter can enhance DBP formation and toxicity-weighted values. Acid conditions showed a very high DBP risk, while alkaline conditions could cut this risk obviously, especially for the toxicity-weighted values of these DBPs. Graphical abstract: Image 1 Highlights: Combined chlorine from SMX chlorination can self-degrade and release free chlorine. UV can enhance the degradation of combined chlorine after pre-chlorination of SMX. Pre-chlorination/post-UV treatment of SMX can lead to deamination. Deamination in pre-chlorination/post-UV of SMX can reduce DCAN formation potential. Alkaline condition can reduce DBPs in pre-chlorination/post-UV/final-chlorination.